Dharmalan Dana - Nelson, George (ANU Press, 2014)
A Yorta Yorta man's seventy-three-year search for the story of his Aboriginal and Indian ancestors including his Indian Grampa who, as a real mystery man, came to Yorta Yorta country in Australia, from Mauritius, in 1881 and went on to leave an incredible legacy for Aboriginal Australia. This story is written through George Nelson's eyes, life and experiences, from the time of his earliest memory, to his marriage to his sweetheart Brenda, through to his journey to Mauritius at the age of seventy-three, to the production of this wonderful story in the present.